1998
DOI: 10.1016/s0022-5223(98)70244-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass grafting on the beating heart without the use of extracorporeal circulation: review of 2052 cases

Abstract: On the basis of the presented data, off-pump coronary artery bypass grafting appeared to be a safe and effective technique in selected patients with appropriate coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 10 publications
(9 reference statements)
2
47
0
1
Order By: Relevance
“…[5][6][7] Several large, nonrandomized, retrospective case series comparing CABG surgery performed on the beating heart (off pump) and conventional CABG surgery performed with CPB (on pump) have indicated an advantage to CABG surgery without CPB; however, selection bias toward lower-risk cases in CABG without CPB remains an issue. 8 -14 The largest randomized studies published to date are conflicting, with some demonstrating decreased length of hospitalization and myocardial enzyme release, 15 whereas others demonstrate decreased incidence of atrial fibrillation, length of hospitalization, and blood-product utilization with CABG surgery performed on the beating heart.…”
Section: See P 810mentioning
confidence: 99%
“…[5][6][7] Several large, nonrandomized, retrospective case series comparing CABG surgery performed on the beating heart (off pump) and conventional CABG surgery performed with CPB (on pump) have indicated an advantage to CABG surgery without CPB; however, selection bias toward lower-risk cases in CABG without CPB remains an issue. 8 -14 The largest randomized studies published to date are conflicting, with some demonstrating decreased length of hospitalization and myocardial enzyme release, 15 whereas others demonstrate decreased incidence of atrial fibrillation, length of hospitalization, and blood-product utilization with CABG surgery performed on the beating heart.…”
Section: See P 810mentioning
confidence: 99%
“…In addition, off-pump enables decreases in blood loss and blood and blood products, length of the intensive care unit stay, and hospital stay. 23,24) Our approach using off-pump had a shorter intubation time, shorter intensive care unit stay, and shorter hospital stay (Table IV). In all patients, we performed CEA before CABG in order to avoid hemodynamic disturbances in the carotid circulation while using the off-pump.…”
Section: Discussionmentioning
confidence: 90%
“…The rise in pulmonary artery pressure is followed by a drop in systolic pressure and a significant decrease in myocardial contractility, 2 compromising the safe completion of the procedures without cardiopulmonary bypass (CPB). Respiratory insufficiency accounts for one tenth (4/39) of the causes of early postoperative death in 2,052 patients receiving OPCAB surgery as reported by Tasdemir et al 3 A transesophageal echocardiographic study showed that a five-minute coronary occlusion was associated with significantly elevated left ventricular wall motion score and concomitant significantly increased pulmonary artery pressure in patients undergoing OPCAB surgery. 4 Other laboratory findings have shown that coronary artery occlusion caused pulmonary damage that was worsened by coronary reperfusion.…”
Section: Conclusion : Le Peo Par Occlusion Transitoire De L'artère Ilmentioning
confidence: 90%